Focal therapy of prostate cancer. Issue 6 (November 2018) - Hübner, Nicolai; Shariat, Shahrokh F.; Remzi, Mesut
Abstract : Purpose of review: The aim of this study was to summarize the latest evidence, as well as the rationale behind using focal therapy for the treatment of prostate cancer. With patients becoming more educated, knowledge of the available evidence is key when discussing treatment. Recent findings: In older works, the natural history of prostate cancer has been described as being multifocal, driven by one index lesion. This represents the key argument for most experts, why focal therapy is feasible in prostate cancer. Most modalities have similar results. For high-intensity focussed ultrasound (HIFU), a pooled data analysis with a median follow-up of 2.2 years showed a negative biopsy rate of 77% with a salvage therapy free rate of 92%. A matched pair analysis comparing irreversible electroporation with robot-assisted radical prostatectomy showed a better side effect profile for focal therapy in evenly matched groups, yet with worse disease-free survival. Interestingly, the better outcomes concerning continence and erectile function did not translate into better patient-reported outcomes. Summary: Focal therapy modalities are generally well tolerated and show good results in terms of continence and potency. Long-term follow-up is not available, and inclusion criteria for trials are not yet uniform. Newer technologies, such as photodynamic therapy, are being developed, as well as improvements to older techniques, such as HIFU.